Casa Zaharya (2003)
Vivienda unifamiliar en Bariloche, Neuquén, frente al lago Nahuel Huapi
Keywords: ARGENTINA; SAN CARLOS DE BARILOCHE; VIVIENDAS DE VACACIONES; VIVIENDAS UNIFAMILIARES; VIVIENDAS EN BOSQUES; DERGARABEDIAN, GUILLERMO; FRANGELLA, ROBERTO